The program packages for primer information processing, identification of the dynamic characteristic, choosing optimal working regime and design of the agricultural machines - Lang, Pham Van; My, Nguyen Huy; Anh, Nguyen Tuan; Chau, Tran Minh; Hung, Le Sy; Hung, Nguyen Thai (Journal of Computer Science and Cybernetics, 2015)
-